2017
DOI: 10.1016/j.neurobiolaging.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG during normal aging: association with the Alzheimer's disease genetic risk variant in PICALM gene

Abstract: Genome-wide association studies have identified novel risk variants for Alzheimer's disease (AD). Among these, a gene carrying one of the highest risks for AD is PICALM. The PICALM rs3851179 A allele is thought to have a protective effect, whereas the G allele appears to confer risk for AD. The influence of the PICALM genotype on brain function in nondemented subjects remains largely unknown. We examined the possible effect of the PICALM rs3851179 genotype on quantitative electroencephalography recording at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…Our findings are consistent with previous research showing an overall agerelated reduction of theta activity (Supplementary Material 1; Matousek et al, 1967;Duffy et al, 1984Duffy et al, , 1993Breslau et al, 1989;Williamson et al, 1990;Hartikainen et al, 1992;Widagdo et al, 1998;Cummins and Finnigan, 2007;Volf and Gluhih, 2011;Vysata et al, 2012;Van de Vijver et al, 2014;Reichert et al, 2016;Barry and De Blasio, 2017;Trammell et al, 2017). Some studies also reported that theta relative power was relatively stable across ages in the eyes closed condition (Penttila et al, 1985;Giaquinto and Nolfe, 1986;Hartikainen et al, 1992;Widagdo et al, 1998;Reichert et al, 2016;Ponomareva et al, 2017). This is consistent with our findings that the age-group difference in theta relative power is less prominent in the eyes closed condition.…”
Section: Theta-bandsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous research showing an overall agerelated reduction of theta activity (Supplementary Material 1; Matousek et al, 1967;Duffy et al, 1984Duffy et al, , 1993Breslau et al, 1989;Williamson et al, 1990;Hartikainen et al, 1992;Widagdo et al, 1998;Cummins and Finnigan, 2007;Volf and Gluhih, 2011;Vysata et al, 2012;Van de Vijver et al, 2014;Reichert et al, 2016;Barry and De Blasio, 2017;Trammell et al, 2017). Some studies also reported that theta relative power was relatively stable across ages in the eyes closed condition (Penttila et al, 1985;Giaquinto and Nolfe, 1986;Hartikainen et al, 1992;Widagdo et al, 1998;Reichert et al, 2016;Ponomareva et al, 2017). This is consistent with our findings that the age-group difference in theta relative power is less prominent in the eyes closed condition.…”
Section: Theta-bandsupporting
confidence: 93%
“…Fan et al (2014) reported no difference between theta power (4-8 Hz) at rest with the eyes closed between older (mean age: 74.24; N = 9) and young (mean age: 35.14; N = 16) adults, but no data were shown. Their young adult group was 10 years older than in the current study, so it is interesting to note that most studies comparing older adults with young adults around 30 years of age failed to show age-related differences in theta activity during eyes closed recordings, suggesting that theta activity might already be decreasing by 30 years of age (Penttila et al, 1985;Hartikainen et al, 1992;Widagdo et al, 1998;Ponomareva et al, 2017). Oken and Kaye (1992) reported a positive correlation between age and theta relative power (4.25-8 Hz) in a population of healthy adults between 20 and 99 years of age.…”
Section: Theta-bandmentioning
confidence: 61%
“…Our previous studies have shown that the PICALM genotype is associated with characteristics of rsEEG beta power and with latency of P300 cognitive evoked potentials. The carriers of the PICALM GG genotype have a more pronounced increase in ERP P300 latency and higher rsEEG beta power compared to the carriers of the PICALM A allele (Ponomareva et al, 2017;Ponomareva et al, 2018). These effects were more pronounced in non-demented subjects older than 50 years of age, whereas the difference in LLC characteristics of alpha sources was observed in younger subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Genomic DNA was isolated from peripheral venous blood using a standard phenol-chloroform extraction method or a Qiagen DNA isolation kit (Qiagen, Netherlands). PICALM genotyping was performed by PCR followed by restriction fragment length polymorphism (RFLP) analysis as previously described (Ponomareva et al, 2017). ApoE genotyping was performed using PCR followed by RFLP analysis.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation